2022
DOI: 10.1021/acs.jmedchem.2c01493
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclic SpiroLactams Kill Mycobacteria In Vitro and In Vivo by Inhibiting Type II NADH Dehydrogenases

Abstract: It is critical that novel classes of antituberculosis drugs are developed to combat the increasing burden of infections by multidrug-resistant strains. To identify such a novel class of antibiotics, a chemical library of unique 3-D bioinspired molecules was explored revealing a promising, mycobacterium specific Tricyclic SpiroLactam (TriSLa) hit. Chemical optimization of the TriSLa scaffold delivered potent analogues with nanomolar activity against replicating and nonreplicating Mycobacterium tuberculosis. Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A focused library of new three-dimensional tricyclic spirolactams is currently produced and screened on a variety of biological targets. Among them, several compounds have already been identified as lead compounds against mycobacteria [ 47 ]. The structure-activity relationship studies will be reported soon.…”
Section: Discussionmentioning
confidence: 99%
“…A focused library of new three-dimensional tricyclic spirolactams is currently produced and screened on a variety of biological targets. Among them, several compounds have already been identified as lead compounds against mycobacteria [ 47 ]. The structure-activity relationship studies will be reported soon.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, expression of Nox rescued wild-type Mtb from Ndh-1/Ndh-2 synthetic lethality, further confirming that NADH oxidation is the main biological function of NADH dehydrogenases regarding bacterial viability. Several potent Ndh-2 inhibitors have been identified (10)(11)(12)(13)(14)(15)(16). ndh-2 susceptibility to long-chain fatty acids in the medium, an important carbon source during infection, and to hypoxic conditions (9) argues for Ndh-2 inhibitors to be effective in specific microenvironments like the necrotic center of caseating granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to phenothiazines, which we later showed to inhibit Mtb's in vitro growth independently of Ndh-2 (9), multiple small molecules have been proposed to specifically inhibit Ndh-2 in Mtb: quinolones (10), quinolinyl pyrimidines (11), molecules with thioquinazoline and tetrahydroindazole cores (12), diphenyleneiodonium analogues (13), 2-Mercapto-Quinazolinones (14), 7-phenyl benzoxaborole compound series (15), and, more recently, tricyclic spirolactams (16). However, the activity of these compounds against Mtb was only demonstrated in in vitro conditions and an Mtb strain in which both genes encoding Ndh-2 enzymes have been deleted (Mtb ndh-2) is only mildly attenuated in a mouse model of infection, suggesting that inhibition of Ndh-2 alone will not kill Mtb during infection (9).…”
Section: Introductionmentioning
confidence: 99%
“…Electrons enter this metabolic pathway via NADH dehydrogenase, thereby oxidizing NADH to NAD + . [16][17][18][19] Mtb possesses two types of NADH dehydrogenase, type I and type II (ndh and ndhA). From a genetic knockout study of ndh and ndhA, the indispensable role of ndh in the unaltered functioning of the oxidative phosphorylation pathway has been reported.…”
Section: Introductionmentioning
confidence: 99%